Pengaruh Pemberian Air Kelapa Muda terhadap Tekanan Darah pada Pasien Hipertensi - V.M. Endang S.P. Rahayu; I Made Mertha; I Gusti Ayu Ari Rasdini; I Dewa Putu Gede Putra Yasa (Jurnal Gema Keperawatan, 2021)
Hypertension is often called the “silent killer”. Hypertension is a condition when blood pressure in blood vessels continues to increase chronically where systolic blood pressure ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg. Hypertension can be controlled with non pharmalocogical treatment, one of them is young coconut water, because the content of potassium contained in young coconut water is very useful to reduce systolic and diastolic blood pressure. This study aims to determine the effect of giving young coconut water against blood pressure in hypertension patients at UPTD Puskesmas 1 South Denpasar 2021. The type of this research was pre-experimental design with one group pretest-post test design using non probability sampling with purposive sampling. The number of sampels were 11 people. The study was conducted on April 2021. The result showed the mean systolic blood pressure and diastole before treatment 149,45/95,73 mmHg and after treatment 140,73/89,45 mmHg. Hypothesis testing used paired t-test with a value of p=0,000 0,05. It can be concluded that there is the effect of giving young coconut water on blood pressure in hypertension patients at UPTD Puskesmas 1 South Denpasar. Patients with hypertension should be able to use young coconut water as a cheap and efficient non-pharmacological therapy to lower blood pressure.